Implikasi Penanaman Kesadaran Berinfak Terhadap Sikap Altruisme dan Qona’ah pada Santri SMP di Pondok Pesantren Nurul Islam Tengaran Kabupaten Semarang - Mulyani, Sri; Prakoso, Nursyah Bani (Attractive : Innovative Education Journal, 2022)
This aims to find out the method used in instilling awareness of giving in an effort to increase the attitude of altruism and qana’ah in students carried out by the pesantren builder at the Nurul Islam Tengaran Islamic boarding school, Semarang Regency. This research methodology is qualitative by using a naturalistic qualitative approach. Sources of data obtained are primary and secondary data sources. Data collection through interview, observation and documentation techniques. The analysis technique is by reducing data, analyzing data and drawing conclusions. The results showed that the method used by the pesantren builder in instilling awareness of giving to the students at the Nurul Islam Tengaran Islamic boarding school, Semarang district, was by applying the exemplary method, the habituation method, the advice method and the supervision method. Supporting factors in instilling awareness of donations are the role of pesantren supervisors as mentors and pesantren activities such as Friday donations, halaqoh tarbawi (liqo), fundraising, charity concerts and breaking fast together. Meanwhile, the inhibiting factors in instilling this awareness of giving are the internal factors of students and peer factors. As for the impact of instilling awareness of giving in an effort to increase altruism, it is shown that students are more concerned with others and pesantren leaders who are in trouble/afflicted by disasters without expecting anything in return, share more often with peers and offer assistance, are more sensitive to the surrounding environment. While the increase in the attitude of qanaah is shown that students are more grateful for what they have, are more patient when they get a disaster, and accept whatever God has given them so they can avoid lust, greed and other despicable behavior. Keywords: Cultivation of Awareness, Cultivating Attitude Altruism, Cultivating Qona’ah